New ionic liquids based on systemic acquired resistance inducers combined with the phytotoxicity reducing cholinium cation. (21st June 2018) - Kukawka, R.; Czerwoniec, P.; Lewandowski, P.; Pospieszny, H.; Smiglak, M.
Abstract : Systemic acquired resistance (SAR) is one of the most promising ways to support plants in the fight against viruses. Abstract : Systemic acquired resistance (SAR) is one of the most promising ways to support plants in the fight against viruses. Using this approach biological or chemical factors interact with plants and stimulate their immune system against infections before infection occurs. This paper presents synthesis, physical properties, phytotoxicity and SAR induction efficacy of 15 ionic liquids, derivatives of SAR inducers paired with the cholinium cation, an essential nutrient for organisms. SAR induction efficacy tests were performed on tobacco Nicotiana tabacum var. Xanthi infected by tobacco mosaic virus (TMV).